2008
DOI: 10.1016/j.apmr.2008.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Osteoporosis in Osteoarthritic Patients Undergoing Total Hip or Total Knee Arthroplasty

Abstract: Objective-To determine the prevalence of osteoporosis in osteoarthritic patients undergoing total hip or total knee arthroplasty.Design-Cross-sectional study. Setting-The Specialized Outpatient Rehabilitation Service's (SORS) Pre-surgical ArthroplastyService located at the Chedoke Hospital, Hamilton Health Sciences, Hamilton, ON, Canada. Participants-SORS outpatients (N=364), from the period of March 2006 to March 2007. Interventions-Not applicable.Main Outcome Measures-Prevalence of osteoporosis was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 9 publications
1
23
0
1
Order By: Relevance
“…L ow bone mineral density (BMD) appears to be common in patients undergoing total joint replacement (TJR), with up to two thirds and one third meeting criteria for osteopenia and osteoporosis, respectively. [1][2][3][4][5][6][7][8][9] Emerging data raise concerns that low BMD may increase the risk of intraoperative and postoperative complications in patients undergoing TJR. In a study of total ankle arthroplasty, low tibial BMD, as measured by Hounsfield units, from preoperative ankle computed tomography scan was associated with a higher risk for periprosthetic fracture (P=.018), with all intraoperative fractures occurring in patients with tibial Hounsfield units less than 200.…”
mentioning
confidence: 99%
“…L ow bone mineral density (BMD) appears to be common in patients undergoing total joint replacement (TJR), with up to two thirds and one third meeting criteria for osteopenia and osteoporosis, respectively. [1][2][3][4][5][6][7][8][9] Emerging data raise concerns that low BMD may increase the risk of intraoperative and postoperative complications in patients undergoing TJR. In a study of total ankle arthroplasty, low tibial BMD, as measured by Hounsfield units, from preoperative ankle computed tomography scan was associated with a higher risk for periprosthetic fracture (P=.018), with all intraoperative fractures occurring in patients with tibial Hounsfield units less than 200.…”
mentioning
confidence: 99%
“…The quantity and quality of cancellous bone vary widely among individuals. Many patients are not considered candidates for cementless total knee arthroplasty because of concerns about insufficient cancellous bone in the proximal part of the tibia [13][14][15][16] . Biological enhancement of cancellous bone quantity and osseointegration would provide one mechanism to improve the outcomes of cementless total knee arthroplasty.…”
mentioning
confidence: 99%
“…Others detected no correlation between BMD at OA sites and at sites distant from the osteoarthritic site without OA. (36, 18, 37). Our previous studies showed that women with unilateral hip OA have lower BMD levels on the contralateral side, with discordance in osteoporosis classification according to BMD measures (15, 20).…”
Section: Discussionmentioning
confidence: 99%
“…A further analysis of the characteristics in study subjects showed that those with both OA and OP had significantly lower body weight and BMI, and were older than those without OP (16). Subsequent reports confirmed that 20% to 29% of men and women with advanced OA have occult OP (17, 18, 19). …”
Section: Introductionmentioning
confidence: 89%